A Study of Health-Promoting Behaviors of Medical Sciences Students of Islamic Azad University of Sari, Iran 2013 - Ghahraman Mahmoodi; Mohammad Ali Jahani; Masoome Naghavian; Azimeh Nazari; Narjes Ahmadi (علوم بهداشتی ایران)
Abstract Background and purpose:Health-promoting activities and a healthy lifestyle are major strategies to preserve health. The purpose of this research study, health-promoting behaviors of medical sciences student of Islamic Azad University of Sari, Iran, was carried out in order to determine the compliance and to promote the medical community. Materials and Methods:This was a cross-sectional study conducted on 285 university students, School of Medical Sciences, Sari, Iran, who were selected using stratified random sampling. Tools for data collection questionnaire were health-promoting lifestyle profile-II, which includes two main categories of health behaviors and psychosocial health of six sub-categories. Data were entered into the SPSS statistical software and for analysis, Friedman and One-sample test was used. Results:Of the six dimensions of health-promoting behaviors, spiritual growth, averaging 25.11 ± 4.57 most, and the area of physical activity with a mean 18.33 ± 4.40 was the lowest score accounted in this study. The results of Freidman test showed that the ranking of dimensions (aspects) are as following: 1 - personnel inter-relationship 2 - spiritual growth 3 - nutrition 4 - management stress 5 - health responsibility and 6 - physical activity. Conclusion:The finding was shown that doing the facilitator behavior and health promotion in the students are at the acceptable level. Furthermore, the terms of personnel inter-relationship, spiritual growth, nutrition, and stress management are at the important level of health promotion aspects. Regarding the above situations of health-promoting behaviors for health education programs among medical group students is recommended.